Potential health risks via consumption of six edible shellfish species collected from Piura – Peru - Loaiza I. (2018)
Sincere thanks to the ACQUAPISCO SA. staff members and interns for their support during the Summer Sampling Campaign I. We would like to thank Joosen Steven and Valentine Mubiana for their help in metal analysis. This research is in frame of the joint Ph.D. research (MACOPSproject) of Iván Loaiza Alamo at Ghent University (UGent) and University of Antwerp (UAntwerp), and was supported and financed by Cienciactiva, initiative from the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica (CONCYTEC), Peru. Contrato 214-2015-FONDECYT.